2018
DOI: 10.1007/s10815-018-1189-2
|View full text |Cite
|
Sign up to set email alerts
|

Social media in the REI clinic: what do patients want?

Abstract: Patients are interested in the use of social media as a forum for patient education and support in the infertility clinic. Patient preferences regarding post topics should be carefully considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Giving responsibility to men to be involved in men's health promotion in the community might also improve the confidence and esteem of local men. The results of a previous study support this finding, showing that giving responsibility to an individual in the community, such as a community health champion role, can serve as a catalyst for change at the individual and community levels [35]. In addition, the relationship between men and providers can be improved if the clinic has a social media account and uses it to interact with the community.…”
Section: Discussionmentioning
confidence: 61%
“…Giving responsibility to men to be involved in men's health promotion in the community might also improve the confidence and esteem of local men. The results of a previous study support this finding, showing that giving responsibility to an individual in the community, such as a community health champion role, can serve as a catalyst for change at the individual and community levels [35]. In addition, the relationship between men and providers can be improved if the clinic has a social media account and uses it to interact with the community.…”
Section: Discussionmentioning
confidence: 61%
“…Research of Arielle H. Bayer was performed while at New York University and manuscript completed while at Albert Einstein College of Medicine Reproductive-aged women are avid consumers of social media and the internet, with 73% of adult women in the USA using social media [3]. Patients generally view the social media healthcare space favorably-a survey of patients in an infertility clinic showed 79.9% of respondents felt social media benefitted the patient experience [4]. A recent study of couples desiring children and actively trying to conceive found that participants were most likely to seek fertilityrelated information on the internet as a first source [5].…”
Section: Introductionmentioning
confidence: 99%
“…Eighty percent of survey respondents felt that social media improved their overall patient experience in the infertility clinic. The majority (60 %) of survey respondents used Instagram [ 21 ].…”
Section: Discussionmentioning
confidence: 99%